Reduced Software Complexity for E-Government Applications with ZEF Framework - Ahmad Nurul Fajar; Imam Marzuki Shofi (Universitas Ahmad Dahlan, 2017)
The situation of dynamic change is unpredictable and always growth increasingly. It also can happen anytime and anywhere. The one kind which is always changing is the government policy.This condition is suggested take the impact for software for information system. It will cause replacement, modification, and enhancement of software for information system. There is some commonality and variability of software features in Indonesian Government. Hence, to manage it, we present enhancement of Zuma’s E-Government Framework (ZEF) for reduce software complexity.We enhance ZEF Framework using SPLE and GORE approach in order to improve traditional software development.It can reduce, if the changing continuously happen.The measurement of software complexity relate to functionality of system.It can describe with function point, because function point can describe logical software complexity also. The preliminary result of this study can reduce efficiency of software complexity such as information processing size, technical complexity adjustment factors and function points in e-government applications.